HUBUNGAN PERILAKU PEMBERIAN MP-ASI DAN KEJADIAN DIARE DENGAN STATUS GIZI ANAK USIA 6-24 BULAN DI RSIA PKU MUHAMMADIYAH CIPONDOH - Susanti, Tazkiyyah Khanifah; Dewanti, Lintang Purwara; Sitoayu, Laras; Nuzrina, Rachmanida (Jurnal Gizi dan Pangan Soedirman, 2023)
Based on RISKESDAS 2018, diarrhea prevalence in Banten was 7.5%. While national prevalence was 6.8%. Diarrhea is the number one causal of inpatients at Indonesian hospitals. Incorrect breastfeeding and complementary feeding practices were some causal of nutritional problems. Complementary feeding practices need a proper delivery time, frequency, type, foods amount, and how to made. This was due to mothers’ ignorance of benefits and the correct way of giving complementary feeding so that it affects the mother's attitude. This study aimed to know the correlation of complementary feeding practices and diarrhea incidence toward nutrition status for infants at 6-24 months of age at RSIA PKU Muhammadiyah Cipondoh. This is a descriptive quantitative study with cross-sectional approach using primary data through interview with questionnaire and Recall 24-Hours. Total sample of infants (6-24 months of age) were 80. Statistical data processed using chi-square test. Data statistically showed that the age of complementary feeding had pValue=0.589, frequency with pValue=0.193, total energy intake pValue=0.22, OR=0.754, total protein intake p=0.016, OR=4.952, texture pValue=0.341, portion pValue=0.009, and the incidence of diarrhea had pValue=0.079. There was a correlation between total energy intake, protein intake, and portion of complementary foods toward nutrition status at RSIA PKU Muhammadiyah Cipondoh. Keywords: complementary feeding practices, diarrhea, nutrition status